High CO2 Adsorption Enthalpy Enabled by Uncoordinated N-Heteroatom Sites of a 3D Metal-Organic Framework. (21st December 2019) - Zhao, Yongting; Xie, Yiming
Abstract : A 3D metal-organic framework (MOF), Mn2 L2 (H2 O)2 · (DMF) H2 L = 5- (Pyridin-2-yl)-3, 3′-bi (1H-1, 2, 4-triazole) (1 ) with uncoordinated N-heteroatom sites, has been obtained through hydrothermal method and structurally characterized by X-ray structural analysis, powder X-ray diffraction (PXRD), and thermal analysis (TGA). The framework of compound 1 exhibits fascinating adsorption properties and shows high adsorption enthalpy of CO2 . The experimental results prove which uncoordinated nitrogen heteroatom sites can markedly increase the reciprocity between host frame and CO2 at room temperature.